Factors Affecting Adverse Drug Reaction Reporting of Healthcare Professionals and Their Knowledge, Attitude, and Practice towards ADR Reporting in Nekemte Town, West Ethiopia - Gurmesa, Lense Temesgen (Biomed Res Int, 2016)
Background. Adverse drug reactions are global problems of major concern. Adverse drug reaction reporting helps the drug monitoring system to detect the unwanted effects of those drugs which are already in the market. Aims. To assess the knowledge, attitude, and practice of health care professionals working in Nekemte town towards adverse drug reaction reporting. Methods and Materials. A cross-sectional study design was conducted on a total of 133 health care professionals by interview to assess their knowledge, attitude, and practice using structured questionnaire. Results. Of the total respondents, only 64 (48.2%), 56 (42.1%), and 13 (9.8%) health care professionals have correctly answered the knowledge, attitude, and practice assessment questions, respectively. Lack of awareness and knowledge on what, when, and to whom to report adverse drug reactions and lack of commitments of health care professionals were identified as the major discouraging factors against adverse drug reaction reporting. Conclusion. This study has revealed that the knowledge, attitude, and practice of the health care professionals working in Nekemte town towards spontaneous adverse drug reaction reporting were low that we would like to recommend the concerned bodies to strive on the improvement of the knowledge, attitude, and practice status of health care professionals.